Observations of conjugate MSTIDs using networks of GPS receivers in the American sector. Issue 9 (16th September 2016) - Valladares, C. E.; Sheehan, R.
Abstract: This study has used total electron content (TEC) values from an extended network of GPS receivers and a highly developed processing to characterize the conjugacy of medium‐scale traveling ionospheric disturbances (MSTIDs) over the American continent. It was found that midlatitude nighttime MSTIDs, also named electrobuoyancy waves, map into the opposite hemisphere but the amplitude of the TEC disturbance in the Southern Hemisphere is between 8 and 13% of the amplitude in the original hemisphere. The periods of the MSTIDs vary between 50 and 65 min. MSTID dynamics is presented for two days: 20 August 2012 and 17 June 2012. On the first day, MSTIDs entered into the American sector shortly before 4 UT, last for 3 h, drifted at an average speed of 200 m/s, and dissipated in the Caribbean region. In the Northern Hemisphere, the MSTIDs were directed southwestward (SW) and 60° from south. In the Southern Hemisphere, they moved northwestward (NW) or 60° from north. The MSTID velocity changed through the night from 300 m/s to 150 m/s, but the propagation direction did not vary. On 17 June 2012 a series of wide MSTIDs were seen traveling across the Caribbean region that exited through the western coast of Central America. These MSTIDs last for 5 h. Number density measured with the DMSP‐F15 and DMSP‐F17 satellites confirm the notion that the MSTIDs consist of rising and falling sheets of plasma density driven by electric fields likely set by a Perkins‐type instability. These observations support the notion that gravity waves can seed and boost the growth of the nighttime MSTIDs. Key Points: Observations of conjugate nighttime MSTIDs (electrobuoyancy waves) during magnetically disturbed periods GPS TEC signatures of MSTIDs in two opposite hemispheres under different interhemisphere background conditions Evidence of interhemispheric coupling of MSTIDs in the American Sector